- The educational and economic return of the institutions of higher education in Algeria - descriptive study - Gherbia, Samra (Journal of Educational and Psychological Sciences, 2018)
The concept of educational return extends to dimensions other than the outcome of school results for secondary education institutions success or failure of the study, expressed in the rates and totals obtained in the school and official exams, they are only quantitative indicators of educational return, To take into account the abilities of learners in applying the content of the curriculum, and to supplement the annual academic programs that affect the achievement of the school negatively or positively, and other aspects are at the core of the educational goals set by the community most important related to human values ​​and ethics and high System and discipline within schools. The purpose of this descriptive study is to describe the reality as it is based on a descriptive approach that works to diagnose the educational phenomenon shed light and clarify the importance of the phenomenon of educational returns to educational institutions and that it is broader than absorbed by applied pedagogy research. It is a social phenomenon because the educational institution is a social institution that plays a structurally interrelated role It is the official tool of education. We have concluded that the negative results of reform and improvement of quality in the higher education sector in Algeria exceeded the positive results, especially with regard to the deterioration of the educational level of the certificate holders, and the departure of foreign competencies with random employment policies to fill the vacuum. These negatives in reform are due to several reasons, the most important of which are: 1- The reform decision is more political than economic. 2 - not limit the technical and pedagogical means that help to achieve this reform and the reform of higher education without reforming the educational system. In addition, when harnessing all the material and human resources and the participation of all parties in the work of the administration, professors and students in the work leads to the total commitment to improve the developmental return in the educational and economic fields and achieve a comprehensive quality in the educational institution, Algeria has not succeeded to a great extent in this area to rely on tradition For European and Western programs and policies. The methodology of the study included the following: 1. The educational return of institutions of higher education as a first subject and the second subject: The necessary requirements for improving the output of the higher education sector. The third is the output of the higher education sector and its relation to economic development. Fourth: Ensuring the quality and international experiences in higher education institutions. Higher education in light of the current circumstances.